The Art of Communication: A Holistic Approach to Counselling of Persons Diagnosed with Terminal Sicknesses in University of Uyo Teaching Hospital - Olutayo, Farinde, Rhoda; Celina, Lawal Omoyemi; Ridwan, Mamud Bola (Journal of Innovation in Education and Social Research, 2024)
This comprehensive study examines the critical role of communication in counselling persons diagnosed with terminal sickness at the University of Uyo Teaching Hospital, Nigeria. The research explores the unique challenges and opportunities in providing effective end-of-life care within the Nigerian cultural context. Through an extensive literature review and analysis, the study investigates various aspects of counselling, including the importance of effective communication techniques, cultural and religious considerations, and the impact of resource limitations on care delivery. The research highlights the significance of a holistic approach to patient care, emphasizing the integration of physical, emotional, social, and spiritual support. It addresses the complexities of truth-telling, family involvement in decision-making, and the ethical considerations surrounding end-of-life care in Nigeria. Furthermore, the research explores innovative solutions such as the integration of technology in counselling services and the establishment of support networks for healthcare providers. The findings underscore the urgent need for improved palliative care services in Nigerian hospitals, calling for increased resource allocation, policy development, and research in culturally sensitive counselling methods. This study contributes valuable insights to the growing body of knowledge on palliative care in Nigeria and offers practical recommendations for enhancing the quality of life for persons diagnosed with terminal sickness. It serves as a foundation for future research and policy development in end-of-life care within the Nigerian healthcare system.